The practice of strategy from Alexander the Great to the present - Olsen, John Andreas, 1968-; Gray, Colin S. (Oxford : Oxford University Press, 2011)
This text focuses on grand strategy and military strategy as practiced over an extended period of time and under very different circumstances, from the campaigns of Alexander the Great to insurgencies and counter-insurgencies in present-day Afghanistan and Iraq.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Keywords: Strategy -- History